Insights into drumlin development from ground-penetrating radar at Múlajökull, Iceland, a surge-type glacier. Issue 259 (8th October 2020) - Woodard, Jacob B.; Zoet, Lucas K.; Benediktsson, Ívar Ö.; Iverson, Neal R.; Finlayson, Andrew
Abstract: Drumlins form at the ice/bed interface through subglacial processes that are not directly observable. The internal stratigraphy of drumlins provides insight into how they developed and associated subglacial processes, but traditional stratigraphic logging techniques are limited to natural exposures and excavations. Using ground-penetrating radar, we imaged the internal stratigraphy of seven drumlins from a recently exposed drumlin field in the forefield of Múlajökull, Iceland. Data were collected with 100 and 200 MHz antennas with maximum resolvable depths of 8 and 4 m, respectively. Longitudinal echograms contained coherent down-ice dipping reflectors over the lengths of the drumlins. Near the drumlin heads (i.e., stoss sides), down-glacier dipping beds lie at high angles to the surface, whereas on the lee sides, the down-glacier dipping beds lie at low angles, or conform, to drumlin surfaces. Transverse echograms exhibited unconformities along the flanks of drumlin heads and conformable bedding across the lee side widths of the drumlins. These observations were ground-truthed with stratigraphic logs from a subset of drumlins and good agreement was found. The stratigraphic patterns support previous conclusions that drumlins at Múlajökull formed on a deformable bed through both depositional and erosional processes which may alternate between its surge and quiescent phases.